2024 Update on Position Statement by Experts from the Polish Society of Allergology and the Polish Respiratory Society on the Evaluation of Efficacy and Effectiveness of Single Inhaler Triple Therapies in Asthma Treatment - Paweł Śliwiński; Adam Antczak; Adam Barczyk; Adam J. Białas; Małgorzata Czajkowska-Malinowska; Karina Jahnz-Różyk; Marek Kulus; Piotr Kuna; Maciej Kupczyk (Advances in Respiratory Medicine)
Medication non-adherence remains a substantial obstacle in asthma care, prompting the exploration of novel therapeutic modalities that prioritize rapid symptom relief, anti-inflammatory activity, and facilitate patients’ compliance. This task is well-served by the following new form of therapy: inhaled triple-combination medications ICS/LABA/LAMA (inhaled glucocorticosteroid/long-acting beta2-agonist/long-acting muscarinic antagonist). The integration of three medications within a singular inhalation device culminates in the reduction of the effective dose of the principal therapeutic agent for asthma management, namely ICS. This consolidation yields a dual benefit of minimizing the likelihood of adverse effects typically linked with ICS while concurrently optimizing bronchodilator efficacy. The accumulated evidence suggests that adding LAMA to a medium- or high-dose ICS/LABA results in a decrease of asthma exacerbations compared to medium- or high-dose ICS/LABA alone, accompanied by sustained enhancements in lung function parameters. In adult patients experiencing suboptimal asthma control despite medium/high-dose ICS/LABA treatment—regardless of adherence to GINA-recommended strategies, such as MART therapy as a first-line approach, or alternative second-line strategies—we propose that the preferred course for intensifying asthma therapy involves the addition of a LAMA, ideally in the form of SITT.